2016
DOI: 10.30955/gnj.001899
|View full text |Cite
|
Sign up to set email alerts
|

Decolarization of methylene blue and methyl orange with Ag doped TiO2 under UV-A and UV-Visible conditions: process optimization by response surface method and toxicity evaluation

Abstract: MB decolarization with pure TiO2 and Ag doped TiO2 based photocatalytic system were investigated under UV-A and UV-Visible conditions. Different ratios of Ag were used as metal dopant. 1% Ag-TiO2 increased the decolorization efficiencies of MB and MO dyes, also the kapp constant enhanced under UV-A and UVVisible conditions. A central composite analysis showed the effect of initial dye concentration, pH, Ag-TiO2 concentration and the reaction time of photocatalytic process under UV-A irridation in both dyes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…AVASARALA et al in the same way found fine crystals aggregated to form irregular shaped particles of magnesium doped titania catalyst with average size of 1.04 µm range [31]. CIFCI observed silver doped titania particles having different shapes of grains with irregular boundaries and many smaller crystals combined to form aggregates [66]. Similarly, Aware and co-workers obtained spherical shaped zinc doped titania nanoparticles with a slight agglomeration [67].…”
Section: Scanning Electron Microscopymentioning
confidence: 86%
See 1 more Smart Citation
“…AVASARALA et al in the same way found fine crystals aggregated to form irregular shaped particles of magnesium doped titania catalyst with average size of 1.04 µm range [31]. CIFCI observed silver doped titania particles having different shapes of grains with irregular boundaries and many smaller crystals combined to form aggregates [66]. Similarly, Aware and co-workers obtained spherical shaped zinc doped titania nanoparticles with a slight agglomeration [67].…”
Section: Scanning Electron Microscopymentioning
confidence: 86%
“…Similarly, SHIVARAJU and co-workers compared Mg-doped titania polyscales with pure titania and found it to be more efficient photocatalyst for the degradation of industrial dyes like methyl violet, methyl red, methyl orange, brilliant green and brilliant blue with 100%, 80%, 79%, 73% and 64% dye degradation respectively [35]. In a study Cifci observed that maximum degradation for methylene blue and methyl orange was achieved with titania nanoparticles doped with 1% silver ions that decreased with further increase in dopant concentration [66].…”
Section: Electron Dispersive X-ray Spectroscopymentioning
confidence: 99%